2011
DOI: 10.1073/pnas.1106106108
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia-induced methylation of a pontin chromatin remodeling factor

Abstract: Pontin is a chromatin remodeling factor that possesses both ATPase and DNA helicase activities. Although Pontin is frequently overexpressed in human cancers of various types and implicated in oncogenic functions, the upstream signaling network leading to the regulation of Pontin that in turn affects transcription of downstream target genes has not been extensively studied. Here, we identify Pontin is methylated by G9a/GLP methyltransferases in hypoxic condition and potentiates HIF-1α-mediated activation by inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
107
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 27 publications
(32 reference statements)
1
107
0
1
Order By: Relevance
“…The histone demethylase jumonji domain (JMJD) containing protein 1A demethylates dimethylated lysine 9 of histone H3 (H3K9me2) and enhances transcription of the HIF-1 target genes SLC2A3 and KDM3A (25). The ATP-dependent chromatin remodeling factors Pontin and Reptin regulate HIF-1 transcriptional activity as well (26,27). Pontin interacts with HIF-1α to enhance transcription of the HIF-1 target gene ETS1, thereby promoting migration of MCF-7 breast cancer cells (26).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The histone demethylase jumonji domain (JMJD) containing protein 1A demethylates dimethylated lysine 9 of histone H3 (H3K9me2) and enhances transcription of the HIF-1 target genes SLC2A3 and KDM3A (25). The ATP-dependent chromatin remodeling factors Pontin and Reptin regulate HIF-1 transcriptional activity as well (26,27). Pontin interacts with HIF-1α to enhance transcription of the HIF-1 target gene ETS1, thereby promoting migration of MCF-7 breast cancer cells (26).…”
mentioning
confidence: 99%
“…The ATP-dependent chromatin remodeling factors Pontin and Reptin regulate HIF-1 transcriptional activity as well (26,27). Pontin interacts with HIF-1α to enhance transcription of the HIF-1 target gene ETS1, thereby promoting migration of MCF-7 breast cancer cells (26). Methylation of Pontin by the histone methyltransferases G9a and GLP is required for coactivator function.…”
mentioning
confidence: 99%
“…A few research groups argued that G9a is upregulated at the post-translational level under hypoxia (23,43), but other groups showed that G9a expression is constant regardless of the O 2 level (44). In fact, we could not observe any change in G9a and GLP expression under moderately and severely hypoxic conditions in all experiments.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15] HIF-1 plays a pivotal role in adaptive responses to hypoxia by modulating various cellular functions through the induction of target genes. [16][17][18][19] Overexpression of HIF-1 has been found in various cancer types and contributes to cancer progression and resistance to therapy.…”
Section: Yang Et Almentioning
confidence: 99%